Organizational form as a source of systemic risk - David Bholat; Joann Gray (Kiel Institute for the World Economy (IfW), 2012)
Systemic risk now occupies centre stage in discussions of bank regulatory reform. Systemic risk is often seen as a problem of size, operational complexity, interconnectivity and contagion. It is less often discussed in terms of the institutional framework of legal rules and principles within which financial intermediation takes place, and the organizational culture promoted by those structures. In this article we redress this deficit through an appraisal of Northern Rock, illustrating the consequences of its transformation from mutually owned building society to publicly held company on organisational culture. These changes had profound effects on the incentive structure of its owners and managers, as profit-maximisation and shareholder value became the driving forces within the firm, as in much of the rest of the UK banking sector. Thus, in addition to grappling with risk and uncertainty - and taking care to distinguish between the two - current efforts to construct a new macro-prudential regulatory paradigm should recognize the importance of Frank Knight's third key conceptual category-profit. Furthermore, in seeking to understand systemic risk, it becomes necessary to delve into micro-legal concepts such as property, trust, and contract that govern different forms of business to discern whether or not some modes of financial association create a greater degree of systemic risk than others. This is especially so when one organizational model comes to dominate retail markets, as did the publicly held company in the UK banking sector at the turn of the twenty-first century.
Keywords: 330; Northern Rock; systemic risk; banks; building societies; UK residential mortgages; Subprime-Hypothek; Finanzmarktkrise; Bank; Unternehmenskultur; Bankrisiko; Systemrisiko; Großbritannien